The perceptions of use of information and communications technologis in working with students with intellectual disabilities in inclusive education - Kovačić, Zoran Miroslav; Milanović-Dobrota, Biljana (Norma, 2023)
The use of information technologis in working with students with intellectual disabilities in the school environment can affect the improvement of their academic, but also competences that can affect their relationship with peers at school. The objective of this research is to examine the perceptions of teachers about the use of information technologis in working with students with intellectual disabilities in an inclusive environment. An additional goal of the research will be to determine certain determinants that can influence these attitudes, such as: gender, years of service, type of job (teacher) and place where the school is located (rural or urban). The sample included 73 respondents who work in primary schools in the territory of the Republic of Serbia. For the purposes of the research, the Teachers' perceptions towards information and communications technologis in teaching-learning process scale was used. The results showed that gender is not statistically significantly related to the perceptions of educators towards the use of information technology. In addition, the place where the school is located, as well as the type of workplace, are also not statistically significantly related. Teachers who have less work experience have statistically significantly more positive attitudes towards the use of information and communications technologis in working with students with intellectual disabilities than their colleagues who have been working in schools longer. The obtained results point to the need for further development of inclusive culture and practice in the school environment, as well as the development of positive perceptions towards the use of new types of technology in working with students with intellectual disabilities in an inclusive environment.
Keywords: modern technology; educators; inclusion